2011
DOI: 10.1245/s10434-011-1638-y
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Cell-Free DNA: A Promising Marker of Pathologic Tumor Response in Rectal Cancer Patients Receiving Preoperative Chemoradiotherapy

Abstract: The plasma levels of the longer fragments (Alu 247) of cfDNA and the cfDNA integrity index are promising markers to predict tumor response after preoperative CRT for rectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
101
3
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 121 publications
(123 citation statements)
references
References 28 publications
8
101
3
2
Order By: Relevance
“…In addition, larger lengths of cell-free DNA and the ratio of larger fragments both increased in the higher TRG scores group, which suggested that these parameters were associated with a better response to preoperative chemoradiotherapy. However, this is not consistent with a previous study, in which lower levels of circulating DNA and lower integrity were found in the responsive group, although this was not statistically significant (16). This difference suggested circulating plasma DNA may originate mainly from tumor necrosis but not active liberation of the tumor itself in rectal cancer.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In addition, larger lengths of cell-free DNA and the ratio of larger fragments both increased in the higher TRG scores group, which suggested that these parameters were associated with a better response to preoperative chemoradiotherapy. However, this is not consistent with a previous study, in which lower levels of circulating DNA and lower integrity were found in the responsive group, although this was not statistically significant (16). This difference suggested circulating plasma DNA may originate mainly from tumor necrosis but not active liberation of the tumor itself in rectal cancer.…”
Section: Discussioncontrasting
confidence: 99%
“…Circulating cell-free DNA fragments from tumor necrosis were variable in size and generally larger than 200 bp. In addition, the ratio between longer fragments and shorter fragments, which was termed the integrity index, was more reliable in reflecting tumor status (16). In the present study, we also demonstrated that plasma cell-free DNA levels were higher in patients with rectal cancer than in healthy individuals, which was consistent with results of previous reports (31).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Patients who responded to chemoradiotherapy, their pre and post treatment cell free DNA integrity indices were found to be statistically different whereas patients who did not respond, their pre and post treatment cell free DNA integrity indices did not differ [54]. Chan et al [55] found that DNA integrity index not only got reduced in patients with nasopharyngeal carcinoma who responded successfully to radiotherapy but was also found to be associated with reduced probability of disease free survival at higher values.…”
Section: Circulating Dna Integrity Index and Its Clinical Significancementioning
confidence: 99%
“…They suggested that integrity index can be a simple and inexpensive way to detect gynecologic and breast cancers. Briefly, integrity index is calculated by amplifying Alu-sequences [48] [54] and nasopharyngeal cancers [55]. Interestingly, in a review focused on circulating DNA integrity index, authors have highlighted the fact that DNA integrity index is more sensitive and specific than circulating DNA concentration in differentiating cancer patients from their respective non-neoplastic diseases and healthy controls [56].…”
Section: Circulating Dna Integrity Index and Its Clinical Significancementioning
confidence: 99%